STUDI KORUPSI DALAM KULTURASI MANAJEMEN MADRASAH DI TUBAN - Mujib Ridlwan (Al Hikmah: Jurnal Studi Keislaman, 2015)
Madrasah (Islamic schools) have a very important role in instilling good values?? and simultaneously preventing the bad and evil ones to the students who will be the successor to the national leadership. Madrasah, formal education institutions introducing Islamic-based curriculum have contributed to the formation of noble character to the students, including the learning of Islamic jurisprudence (fiqh) on the prohibition of stealing (taking the rights of others without getting their permission). Stealing could be be the root of corruption, robbery and so on. If the word 'stealing' means taking the rights of others without getting their permission, but the word 'corruption' is focused more on taking the state-owned money. In essence, the word 'stealing' and 'corruption' have the same meaning taking goods or property that are not theirs or without getting their permission. Madrasah have long taught Islamic jurisprudence on the prohibition of stealing, including sanctions that must be imposed to a thief.